A case report of cardiac neuromodulation in a young patient with a third-degree atrioventricular block - Valenti, Noemi; Di Monaco, Antonio; Romanazzi, Imma; Vitulano, Nicola; Troisi, Federica; Quadrini, Federico; Grimaldi, Massimo (Frontiers in Cardiovascular Medicine, 2024)
Background. There are some functional bradyarrhythmias due to a dysregulation of autonomic nervous system for which a therapeutic strategy of cardioneuroablation (CAN) is conceivable.Case Summary. 19-year-old woman with a non-congenital third degree atrio-ventricular block (AVB), symptomatic for lipothymia and dyspnoea for mild efforts. She has a structurally normal heart and no other comorbidities. The atropine test and the exercise stress test documented a sinus tachycardia at 190 bpm with a 2:1 AVB and a narrow QRS, and an atrioventricular conduction 1:1 until a sinus rhythm rate of 90 bpm. She underwent CNA procedure, targeted the inferior paraseptal ganglion plexus with gradually change of the ECG during the radiofrequency deliver from a third degree AVB to a first degree AVB. After the procedure, we observed a complete regression of the third degree AVB, with only evidence of first degree AVB and complete regression of symptoms until six-month follow-up.Although not yet included in current guidelines, the CNA procedure could be used to treat AV node dysfunctions in young subjects, as it could represents an alternative to the pacemaker implantation. Further randomized studies are needed to assess the long-term efficacy of this promising technique.